2004
DOI: 10.1111/j.1440-1797.2004.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

QTc interval and QTc dispersion during haemodiafiltration

Abstract: In conclusion, the decrease observed in the QTc interval at the end of an AFB session was inversely related to serum Ca++ concentrations. Moreover, an increase in QTc dispersion occurred during the first hour of the session, and was negatively correlated with serum K+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 21 publications
3
26
0
5
Order By: Relevance
“…This phenomenon appears to have different causes, including dialysis-induced electrolyte alterations [16] . Several studies demonstrated how using a dialysis bath with a higher calcium concentration reduces the dispersion of QT and QTc intervals [20] . These intervals and their increased dispersions have been linked to the occurrence of arrhythmias in ESRD patients on HD [7,20] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon appears to have different causes, including dialysis-induced electrolyte alterations [16] . Several studies demonstrated how using a dialysis bath with a higher calcium concentration reduces the dispersion of QT and QTc intervals [20] . These intervals and their increased dispersions have been linked to the occurrence of arrhythmias in ESRD patients on HD [7,20] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated how using a dialysis bath with a higher calcium concentration reduces the dispersion of QT and QTc intervals [20] . These intervals and their increased dispersions have been linked to the occurrence of arrhythmias in ESRD patients on HD [7,20] . This effect could have various causes: regional differences in ventricular wall stress (mechanic-electric or contraction-excitation feedback) caused by ventricular dilation, fibrosis, and calcification, autonomic failure caused by uraemic autonomic neuropathy, decreased circulatory volume, rapid correction of metabolic acidosis, and rapid changes in serum K levels.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, and despite diet advice or medical therapy, patients arrive for their dialysis session with high serum K+ levels, and experience a sudden decrease during the early part of the session. This has been related to the appearance of arrhythmias or to the worsening of pre-existing arrhythmias: induction or worsening of ventricular extrasystoles, QT prolongation (Cupisti , 1999, , Floccari et al, 2004 and onset of paroxysmal atrial fibrillation have been described. Acetate Free Biofiltration with Potassium Profiled Dialysate (AFB-K) is a haemodialysis technique that attempts to obviate this problem, avoiding sudden potassium reductions during the haemodialysis session, but with due correction of the hyperkalaemia of the patients (Santoro et al, 2005).…”
Section: Arrhythmia In Patients On Dialysismentioning
confidence: 99%
“…Bleyer et al [20] reporting on SD in 88 hemodialysis patients found that 13% had serum potassium below 3.5 mEq/l and 6 6.0 mEq/l on routine prior monthly laboratory values. Floccari et al [51] showed that an increase in QT dispersion -which is a risk factor for arrhythmias -during the first hour of HD when arrhythmias frequently occur, was inversely correlated with the rapid removal of potassium. Thus, avoiding rapid electrolyte shifts and dialysate very low in potassium is a sensible strategy to reduce the risk of cardiac arrest in hemodialysis centers but it is unlikely to eliminate the hazard [52] .…”
Section: Avoiding Low Potassium Dialysate and Rapid Electrolyte Shiftsmentioning
confidence: 99%